The nutrition and food‐related roles, experiences and support needs of female family carers of malnourished older rehabilitation patients. Issue 1 (14th July 2016) - Marshall, S.; Reidlinger, D. P.; Young, A.; Isenring, E.
Abstract: Background: To improve perceived value of nutrition support and patient outcomes, the present study aimed to determine the nutrition and food‐related roles, experiences and support needs of female family carers of community‐dwelling malnourished older adults admitted to rehabilitation units in rural New South Wales, Australia, both during admission and following discharge. Methods: Four female family carers of malnourished rehabilitation patients aged ≥65 years were interviewed during their care‐recipients' rehabilitation admission and again at 2 weeks post‐discharge. The semi‐structured interviews were audiotaped, transcribed and analysed reflecting an interpretative phenomenological approach by three researchers. A series of 'drivers' relevant to the research question were agreed upon and discussed. Results: Three drivers were identified. 'Responsibility' was related to the agency who assumed responsibility for providing nutrition support and understanding family carer obligation to provide nutrition support. 'Family carer nutrition ethos' was related to how carer nutrition beliefs, knowledge and values impacted the nutrition support they provided, the high self‐efficacy of family carers and an incongruence with an evidence‐based approach for treating malnutrition. 'Quality of life' was related to the carers' focus upon quality of life as a nutrition strategy and outcome for their care‐recipients, as well as how nutrition support impacted upon carer burden. Conclusions: Rehabilitation units and rehabilitation dietitians should recognise and support family carers of malnourished patients, which may ultimately lead to an improved perceived benefit of care and patient outcomes. Intervention research is required to make strong recommendations for practice.